LEGAL REGULATION OF THE USE OF SMART CONTRACTS IN TRANSBORDER TRANSACTIONS INVOLVING THE TRANSFER OF INTELLECTUAL PROPERTY RIGHTS TO THIRD PARTIES: FOCUS ON UZBEKISTAN - Nodirakhon ABDURAKHMANOVA (Scholar Express Journals, 2024)
This article delves into the legal regulation of smart contracts in transborder transactions involving the transfer of intellectual property (IP) rights, with a particular focus on Uzbekistan's legal landscape. As blockchain technology and smart contracts gain traction, their potential to transform IP transactions is considerable, particularly in a global economy where crossborder exchanges are increasingly common. However, the current legal framework in Uzbekistan presents several challenges, especially regarding jurisdiction, enforceability, and the protection of IP rights. By comparing Uzbekistan’s approach with those of other jurisdictions such as the European Union, the United States, and Singapore, and by examining relevant case law, this article offers practical insights and recommendations for enhancing Uzbekistan's legal infrastructure to better accommodate smart contracts
Keywords: Smart contracts; transborder transactions; intellectual property rights